Nanotechnology-based drug delivery systems for photodynamic therapy of cancer: A review - Calixto, Giovana Maria Fioramonti [UNESP]; Bernegossi, Jéssica [UNESP]; De Freitas, Laura Marise [UNESP]; Fontana, Carla Raquel [UNESP]; Chorilli, Marlus [UNESP]; Grumezescu, Alexandru Mihai (MDPI, 2016)
Photodynamic therapy (PDT) is a promising alternative approach for improved cancer treatment. In PDT, a photosensitizer (PS) is administered that can be activated by light of a specific wavelength, which causes selective damage to the tumor and its surrounding vasculature. The success of PDT is limited by the difficulty in administering photosensitizers (PSs) with low water solubility, which compromises the clinical use of several molecules. Incorporation of PSs in nanostructured drug delivery systems, such as polymeric nanoparticles (PNPs), solid lipid nanoparticles (SLNs), nanostructured lipid carriers (NLCs), gold nanoparticles (AuNPs), hydrogels, liposomes, liquid crystals, dendrimers, and cyclodextrin is a potential strategy to overcome this difficulty. Additionally, nanotechnology-based drug delivery systems may improve the transcytosis of a PS across epithelial and endothelial barriers and afford the simultaneous co-delivery of two or more drugs. Based on this, the application of nanotechnology in medicine may offer numerous exciting possibilities in cancer treatment and improve the efficacy of available therapeutics. Therefore, the aim of this paper is to review nanotechnology-based drug delivery systems for photodynamic therapy of cancer.
Keywords: Cancer; Drug delivery systems; Nanotechnology; Photodynamic therapy